Pola Asuh Orang Tua dan Dampaknya terhadap Perilaku Anak: Studi Kualitatif berdasarkan hasil Konseling Kelompok - Afra Azzahra; Sofyan Abdi; Devi Rizka Nafila; Afra Hasna; Reza Akmalia; Maharani Widawati; Poppy Saadatul Hasanah (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
This study aims to examine the impact of parenting styles on adolescent behavior using a qualitative case study approach within a group counseling setting. The subjects consisted of six adolescents aged 13–15 years from SMPN 17 Bekasi, West Java, Indonesia each with different parenting backgrounds. Data were collected through semi-structured interviews, observation, and documentation, and were validated using triangulation and discussions with the school counselor. The findings indicate that authoritarian, permissive, and neglectful parenting styles negatively affect adolescents' social and emotional behavior, such as anxiety, aggression, withdrawal, and involvement in deviant behaviors. Group counseling helped explore the subjects' experiences and emotions; however, some cases indicated the need for additional intervention through individual counseling. These findings highlight the importance of collaboration between counselors, parents, and schools in establishing parenting styles that support adolescents' positive development.